Venous Aneurysms in Autogenous Hemodialysis Fistulas: Is There an Association with Venous Outflow Stenosis?. Issue 2 (April 2013) - Rajput, Anshu; Rajan, Dheeraj K.; Simons, Martin E.; Sniderman, Kenneth W.; Jaskolka, Jeffrey D.; Beecroft, John R.; Kachura, John R.; Tan, Kong T.
Purpose: To determine whether patients with venous aneurysms in their arteriovenous fistulas (AVFs) have associated venous outflow stenoses. Materials and Methods: A retrospective study was performed, which included all patients presenting with dysfunction and had venous aneurysms in their AVFs. Patient's medical records and imaging studies were examined and data collected including access characteristics, patient demographics and imaging findings. Data were analyzed using Fisher's exact test. Results: A total of 89 patients (58 men, 31 women; mean age 60) presented for intervention related to access dysfunction with incident venous aneurysms over the study period. Of the 89 patients with venous aneurysms (mean diameter 2.3 cm) of their AVF's, 69 (78%) patients had an associated venous outflow stenosis. The stenoses were present most commonly in the outflow cephalic vein (57%), followed by the cephalic arch (20%), brachiocephalic vein (10%) and subclavian vein (6%). Outflow stenoses in AVFs with venous aneurysms were observed in 87% of brachiocephalic AVFs, 60% of radiocephalic AVFs and 80% of brachiobasilic AVFs. Brachiocephalic AVFs with venous aneurysms were significantly more likely to have an associated outflow stenosis than radiocephalic AVFs with venous aneurysms (P=0.007). AVFs with outflow stenosis were on average 1502 days old while AVFs without outflow stenosis were on average 2351 days old, which was a statistically significant difference (P=0.031). No statistically significant differences were observed for sex and side of the fistula. Conclusions: Outflow stenosis was observed to be associated with venous aneurysms in AVFs with a more statistically significant association in brachiocephalic AVFs compared to other AVFs.